Mosses as extraordinary reservoir of microbial diversity: a comparative analysing of co-occurring ‘plant-moss twins’ in natural alpine ecosystem - Dinesh Kumar Ramakrishnan; Birgit Wassermann; Christian Berg; Ahmed Abdelfattah; Gabriele Berg (Environmental Microbiome)
Abstract The decline in plant biodiversity is evident at global scale, but little is known about the loss of microbial diversity associated with diverse plant phyla and their influencing factors. This study investigates the microbial diversity associated with mosses and co-occurring vascular plants in the Alpine ecosystem, focusing on 52 plant “twins” growing on contrasting soil types (carbonate and silicate). Despite co-occurring in the same soil, mosses harbored significantly higher microbial richness and diversity than vascular plants. Across all samples, mosses supporting a total of 3,435 bacterial ASVs and 1,174 fungal ASVs. In contrast, vascular plants hosted a total of 1,760 bacterial ASVs and 911 fungal ASVs. Plant phyla strongly influenced microbial community composition, with vascular plants exhibiting a selective microbial assembly strategy, while mosses showed greater environmental influence. Soil type significantly influenced microbial composition in both plant types, with carbonate soils supporting greater bacterial richness, particularly in mosses. Linear discriminant analysis effect size (LEfSe) analysis highlighted consistent enrichments of Proteobacteria, i.e., Sphingomonadales, Rhizobiales, Burkholderiales and, Pseudomonadales, in vascular plants across soil types, whereas mosses displayed distinct microbial enrichment patterns between carbonate and silicate soils, suggesting a higher environmental connectedness. Our findings demonstrated that plant phyla are a major determinant of the phyllosphere microbiota, and that mosses represent a currently untapped source of microbial biodiversity. This study highlights the importance of considering both host traits and environmental factors for protecting microbial biodiversity and implementing them in global strategies for restoring biodiversity.